Søren Holm: Mythe og kult i Grundtvigs salmedigtning - Johansen, Steen (Grundtvig-studier, 1956)
Søren Holm: Myths and Cult in Grundtvigs Hymns. 1955. By Steen Johansen. Grundtvig’s hymns are distinguished from most other hymn-writing by a much stronger poetic grasp of the religious subject-matter: the discription of Christ’s birth, of His work, His death, His resurrection, etc. This recreation of the religious life and of the sacred acts of the Church Service in his hymns is so powerful that many have called Grundtvig’s hymns “ cult-hymns” and have compared his Christianity, as it is expressed in his hymns, with the cults of the old pre-Christian national religions, whose world philosophy demands a mythology, and whose centre is a mystic action. In these religions the practicing of the cult means the repetition of the mystic action, whereby those who partake in it obtain strength and renewal for their daily life. — Søren Holm seeks to show that this also applies to Grundtvig. But the reviewer considers that Søren Holm has gone a little too far in his attempts to do this. Grundtvig’s world philosophy is not mythological like that of the old national religions, but Biblical, even if Søren Holm wishes to include Christianity and the old national religions in the same classification as mythological. More interesting is his attempt to show the elements of cult in the hymns. Such elements undoubtedly exist. But it is debatable whether they are so pronounced as to overstep the bounds of what is Christian. Søren Holm, however, has no doubt that this is the case.